Peningkatan Penguasaan Kosakata Bahasa Inggris Siswa Kelas XII A MA Plus Nurul Islam Sekarbela Melalui Communicative language Teaching (CLT) - Muhamad Sohibul Hamdani; Dedi Riyan Rizaldi; Lalu Jaswadi Putra; Muktopan Muntahar; Nilwan; Ziadatul Fatimah (Action Research Journal, 2024)
This study aims to improve the English vocabulary mastery of XIIA grade students at MA Plus Nurul Islam Sekarbela through the implementation of the Communicative Language Teaching (CLT) method. The research employed a qualitative approach with a case study design, utilizing observation, interviews, pre-tests, and post-tests as data collection techniques. The findings indicate that the CLT approach, emphasizing real-life communication activities such as role-playing and information gap exercises, effectively enhances students' vocabulary skills. The average post-test scores showed a significant improvement compared to the pre-test, reflecting better understanding and application of vocabulary. Moreover, this approach also increased students' motivation in learning English. Therefore, CLT can be recommended as an effective teaching method to improve English vocabulary mastery at the secondary school level